Pengaruh Infusa Daun Jambu Biji (Psidium guajava Linn.) Terhadap Pertumbuhan Bakteri Escherichia coli Secara In Vitro - Fitri Nadifah; Siti Fatimah; Lisa Susanti (Journal of Health (JoH), 2015)
Background: Diarrhea is still a major health problem in Indonesia. This is due to the lack of knowledge about society hygiene and sanitation as well as there are still many people who haven't got health access. Guava (Psidium guajava) is a plant that has long been known by locals as traditional medicine. Some research has shown that extracts of the guava flesh is effective as an antidiarrheal. In addition, guava possessed efficacy as an anti-inflammatory, anti-mutagenic, anti-microbial and analgesic. Objective: To determine the effect of various concentrations of guava infusion leaves inhibiting E. coli growth in vitro. Methods: Third, fourth and fifth leaf from the tip were used as the materials. Leaves infusion concentration used was 20%, 40%, 60%, 80% and 100%. Each concentration infusion loaded into wells of Mueller-Hinton (MH) agar media. Radical zone around the wells measured as bacterial growth inhibition. The data were analyzed using one way analysis of variance (One-way ANOVAs). Results: There is the influence of infusion of guava leaves (Psidium guajava) on the growth of E. coli in vitro with a mean diameter of the smallest concentration of radicals zone which is 20% of 15.3 mm and the greatest concentration of 100% by 22 mm. Conclusion: Infusion of guava leaves have a strong influence in inhibiting E. coli growth as it has antibacterial chemical components.